Penerapan TCP IP Fiber Optic Menggunakan Topologi Mesh pada Aplikasi Cisco Packet Traser - Rovino Alghafari; Sabila Sofyana Zahra; Vinta Retriani; Alifia Nurfadillah; Didik Aribowo (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2024)
The application of TCP/IP over fiber optic networks with mesh topology has become an interesting topic in the development of modern network infrastructure. This research aims to explore and apply the basic concepts of TCP/IP via fiber optic technology using a mesh topology in the Cisco Packet Tracer simulation. This research method involves building a virtual computer network consisting of several nodes connected via fiber optic cables. The aim of this research is to understand the reliability, efficiency and performance of networks implemented through fiber optic technology and mesh topology. In the initial stage, a literature study was carried out to understand the basic principles of TCP/IP, fiber optic technology, and mesh topology. Next, using Cisco Packet Tracer, a virtual computer network is built using appropriate hardware and software to simulate a fiber optic-based network with a mesh topology. Experiments were conducted to test network performance in terms of data transfer speed, latency, and connection reliability. Experimental results show that the application of TCP/IP over a fiber optic network with a mesh topology is able to provide reliable and efficient performance. The main advantages of using fiber optic technology are high data transfer speeds and better connection reliability compared to other transmission media. In addition, mesh topology provides high flexibility and redundancy in the network, thereby increasing failure tolerance and increasing network scalability.